St. Vincent and the Grenadines : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2010)
St. Vincent and the Grenadines (SVG) is exposed to money laundering (ML) and financing of terrorism (FT) risk related to drug trafficking and international criminal groups. The financing of terrorism has also been criminalized and is largely in conformity with the Suppression of the Financing of Terrorism (SFT) Convention. The legal and institutional framework regarding the cross-border transportation of cash and bearer instruments is largely in place. The preventive measures regime covers most of the financial and designated nonfinancial businesses and professions (DNFBP) sectors as required under the Financial Action Task Force (FATF) Recommendations.